Phenotypic Transitions the Processes Involved in Regulation of Growth and Proangiogenic Properties of Stem Cells, Cancer Stem Cells and Circulating Tumor Cells - Kulus, Magdalena; Farzaneh, Maryam; Bryja, Artur; Zehtabi, Mojtaba; Azizidoost, Shirin; Abouali Gale Dari, Mahrokh; Golcar-Narenji, Afsaneh; Ziemak, Hanna; Chwarzyński, Mikołaj; Piotrowska-Kempisty, Hanna; Dzięgiel, Piotr; Zabel, Maciej; et al. (Stem cell reviews and reports, 2024)
Epithelial-mesenchymal transition (EMT) is a crucial process with significance in the metastasis of malignant tumors. It is through the acquisition of plasticity that cancer cells become more mobile and gain the ability to metastasize to other tissues. The mesenchymal-epithelial transition (MET) is the return to an epithelial state, which allows for the formation of secondary tumors. Both processes, EMT and MET, are regulated by different pathways and different mediators, which affects the sophistication of the overall tumorigenesis process. Not insignificant are also cancer stem cells and their participation in the angiogenesis, which occur very intensively within tumors. Difficulties in effectively treating cancer are primarily dependent on the potential of cancer cells to rapidly expand and occupy secondarily vital organs. Due to the ability of these cells to spread, the concept of the circulating tumor cell (CTC) has emerged. Interestingly, CTCs exhibit molecular diversity and stem-like and mesenchymal features, even when derived from primary tumor tissue from a single patient. While EMT is necessary for metastasis, MET is required for CTCs to establish a secondary site. A thorough understanding of the processes that govern the balance between EMT and MET in malignancy is crucial.
Keywords: Humans; epitelo-mezenchymální tranzice; Neoplastic Cells, Circulating; Phenotype; lidé; nádorové kmenové buňky; Neoplastic Stem Cells; zvířata; proliferace buněk; Epithelial-Mesenchymal Transition; Neovascularization, Pathologic; Stem Cells; fenotyp; Cell Proliferation; Neoplasms; nádorové cirkulující buňky; nádory; kmenové buňky; Animals; patologická angiogeneze